2018
DOI: 10.3389/fphys.2018.00047
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Depletion Protects against Cigarette Smoke-Induced Inflammatory Response in the Mouse Colon and Lung

Abstract: Cigarette smoke (CS) is considered as a major risk factor for pulmonary and intestinal inflammation. CS leads to macrophage infiltration in the mucosae of the lung and colon, inducing the uncontrolled secretion of inflammatory mediators, and thus promoting inflammatory response. In this study, we investigated whether macrophage depletion modulates cigarette smoke (CS)-induced inflammatory response in both the lung and colon. The mice were exposed to CS for 30 min, after which they were rested in a fresh air en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
4
12
0
Order By: Relevance
“…However, intratracheal administration of OVA did not alter IL-17A levels in the colons of WT, T-bet deficient, or IFN-γ deficient mice. The IFN-γ pathway is not the only mechanism linking inflammatory bowel disease and pulmonary inflammation; a recent study demonstrated the role of macrophages in cigarette smoke-induced colitis (35). Indeed, we also observed an increase in the number of macrophages in the colonic laminar propria after OVA sensitization (Supplementary Figure 1), thus detailed mechanisms need to be identified in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, intratracheal administration of OVA did not alter IL-17A levels in the colons of WT, T-bet deficient, or IFN-γ deficient mice. The IFN-γ pathway is not the only mechanism linking inflammatory bowel disease and pulmonary inflammation; a recent study demonstrated the role of macrophages in cigarette smoke-induced colitis (35). Indeed, we also observed an increase in the number of macrophages in the colonic laminar propria after OVA sensitization (Supplementary Figure 1), thus detailed mechanisms need to be identified in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…All cells were stained using cell type-specific mAb. For four months (chronic) exposure, differential cell counts to check the cell influx in neutrophils and macrophages were performed on cytospin slides with Diff-Quick staining (Cui, Liu, Ip, Liang, & Mak, 2020;Lim, Kim, Lee, Bae, & Kim, 2018). The Diff-Quick staining involves sequential dipping of the slides into different solutions -fixative agent (methanol, blue), solution 1 (eosinophilic, orange), and solution 2 (basophilic, blue) followed by rinsing and drying.…”
Section: Differential Cell Count In Bal Fluidmentioning
confidence: 99%
“…Lipopolysaccharide (LPS), a potent endotoxin in gram-negative bacteria, may activate immune cells (such as dendritic cells and alveolar macrophages) during the course of respiratory tract infections via a special type of receptor known as toll-like receptors (TLRs) [11]. Inflammation can also be induced by hypoxia, for example acute hypoxia in rats with endotoxemia results in alveolar macrophages releasing TNF-, IL-1, IL-6, and TLR-4 [12].…”
Section: Introductionmentioning
confidence: 99%
“…The critical role of macrophages in controlling lung inflammation is exemplified by macrophage depletion in mice exposed to cigarette smoke. This results in reduced J o u r n a l P r e -p r o o f Journal Pre-proof inflammatory cell infiltration, ameliorated body weight loss and decreased inflammatory cytokines (IL-1β, IL-6, TNF-α) and the chemokine, monocyte chemoattractant protein-1 in bronchoalveolar lavage fluid (BALF) and reduced matrix metalloproteinase-3 protein expression in lung tissue [11].…”
Section: Introductionmentioning
confidence: 99%